Deletion of SIRT6 in vascular smooth muscle cells facilitates vascular calcification via suppression of DNA damage repair. (December 2022) - Wang, Siyi; Li, Li; Liang, Qingchun; Ye, Yuanzhi; Lan, Zirong; Dong, Qianqian; Chen, An; Fu, Mingwei; Li, Yining; Liu, Xiaoyu; Ou, Jing-Song; Lu, Lihe; et al.
Abstract: Vascular calcification is an important risk factor for cardiovascular events, accompanied by DNA damage during the process. The sirtuin 6 (SIRT6) has been reported to alleviate atherosclerosis, which is related to the reduction of DNA damage. However, whether smooth muscle cell SIRT6 mediates vascular calcification involving DNA damage remains unclear. Western blot and immunofluorescence revealed that SIRT6 expression was decreased in human vascular smooth muscle cells (HVSMCs), human and mouse arteries during vascular calcification. Alizarin red staining and calcium content assay showed that knockdown or deletion of SIRT6 significantly promoted HVSMC calcification induced by high phosphorus and calcium, accompanied by upregulation of osteogenic differentiation markers including Runx2 and BMP2. By contrast, adenovirus-mediated SIRT6 overexpression attenuated osteogenic differentiation and calcification of HVSMCs. Moreover, ex vivo study revealed that SIRT6 overexpression inhibited calcification of mouse and human arterial rings. Of note, smooth muscle cell-specific knockout of SIRT6 markedly aggravated Vitamin D3 -induced aortic calcification in mice. Mechanistically, overexpression of SIRT6 reduced DNA damage and upregulated p-ATM during HVSMCs calcification, whereas knockdown of SIRT6 showed the opposite effects. Knockdown of ATM in HVSMCs abrogated the inhibitory effect of SIRT6 overexpression on calcification and DNA damage. This study for the first time demonstrates that vascular smooth muscle cell-specific deletion of SIRT6 facilitates vascular calcification via suppression of DNA damage repair. Therefore, modulation of SIRT6 and DNA damage repair may represent a therapeutic strategy for vascular calcification. Graphical abstract: Unlabelled Image Highlights: SIRT6 is downregulated during vascular calcification. Knockdown of SIRT6 by siRNA promotes human vascular smooth muscle cell calcification. Overexpression of SIRT6 attenuates calcification of human vascular smooth muscle cells and arterial ring calcification. Smooth muscle cell-specific knockout of SIRT6 aggravates mouse aortic calcification. SIRT6 deficiency contributes to vascular calcification via modulation of p-ATM and suppression of DNA damage repair.